(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of knowledge and practice about diet of type 2 diabetes patients treated as inpatients at Hoai Duc General Hospital and some related factors. Research subjects and methods: A cross-sectional descriptive study was conducted with 115 people with type 2 diabetes treated as inpatients at Hoai Duc General Hospital who met sampling criteria during the period from September to November 2024. Results: The proportion of patients with correct knowledge about the diet of people with diabetes accounted for 70.4%. The proportion of patients who successfully practice their diet is 59.1%. Dietary knowledge is related to dietary practices of people with type 2 diabetes (p < 0.05). Conclusion: In general, knowledge and practice of diet for people with type 2 diabetes is not high. Therefore, hospitals need to strengthen health counseling and education for patients with type 2 diabetes to improve patients’ knowledge and practice of diet.